Data notes on the proteomics of Dendrobium huoshanense under pb treatment - Jun Dai; Yingyu Zhang; Yunpeng Zhang; Yan Wang; Xiaoyuan Ding; Cheng Song (BMC Genomic Data, 2024)
Abstract Objectives Pb stress has a negative impact on plant growth by interfering with photosynthesis and releasing reactive oxygen species, causing major risks such as heavy metal ion accumulation in the soil matrix. A proteomics experiment was conducted to determine whether protein levels of Dendrobium huoshanense changed in response to Pb stress seven to fifteen days after being sprayed with a 200 mg/L Pb (NO3)2 solution. The proteomic data we gathered provides a model for investigations into the mechanisms underlying Dendrobium plant resistance to heavy metal stress. Data description A label-free quantitative proteomics approach was employed to examine the variations in protein expression levels of D. huoshanense at different times of Pb(NO3)2 treatment. We submitted the raw data obtained from these proteomics sequencing experiments to the ProteomeXchange database with the accession number PXD047050. 63,194 mass spectra in total were compared after being imported into the Proteome Discoverer software for database search. A total of 12,402 spectral peptides were identified with a confidence level exceeding 99%, which resulted in the identification of 2,449 significantly differential proteins. These proteins can be utilized for screening, functional annotation, and enrichment analysis of differentially expressed proteins before and after heavy metal treatment experiments.